Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T18:38:23+01:00
1)
a+(a-b) =
a+a-b =
2a-b

2)
2x-(x+4) =
2x-x-4 =
x-4

3)
7-(-x+6) =
7+x-6 =
1+x

4)
-(x+4)+(x-5) =
-x-4+x-5 =
-9

5)
1-(t+p)-(t-2) =
1-t-p-t+2 =
3-2t-p

6)
-(-y+2)+(-2y-4) =
y-2-2y-4 =
-y-6
2010-03-09T18:44:26+01:00
1. a + (a - b) = a + a - b = 2a - b
2. 2x - (x - 4) = 2x - x + 4 = x + 4
3. 7 - (-x + 6) = 7 + x - 6 = x + 7 - 6 = x + 1
4. -(-x + 4) + (x - 5) = x - 4 + x - 5 = 2x - 9
5. 1 - (t + p) - (t - 2) = 1 - t + p - t + 2 = 3 - 2t + p
6. -(-y + 2) + (-2y - 4) = y - 2 + (-2y) - 4 = -y - 6